If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
42 = 6-((2/3)*x) // - 6-((2/3)*x)
(2/3)*x-6+42 = 0
2/3*x+36 = 0 // - 36
2/3*x = -36 // : 2/3
x = -36/2/3
x = -54
x = -54
| 7/10d-21/10 | | 4x-70=12y+2 | | 4p^2-2-p=2-p | | 5x-7x=7 | | -3-12-5+2/3= | | m^4/2m^4 | | 2x/3-5=x-1 | | b/5+1/6=13 | | .25x-2.5=1x+1 | | 6k-1k=5k+10 | | 133=-3(7n+4)-2 | | 10d+9=-7+2(4d+3) | | 5x-2x+4=10 | | 1000(9x-10)=50(656+100x) | | 2(x-7)+x=3(x-6)+4 | | y-60=7x-35 | | (w-6)=3(w+1) | | -12/-4+12/6+3= | | 4x-5x=-4 | | 4x^2+2=402 | | 4y-(-10)=26 | | -6b+8=-8-2(4b+1) | | 5(1-2x)+5=80 | | 7x+-1=2x+5 | | -2x(7-y)+4=-4 | | 9+10(1+7a)= | | -3+4b= | | r=-4 | | -2x(7-y)+7=-4 | | -4(x+1)=-13-4x | | 5/6(18)+3/7(28) | | 36t=78 |